Spending the night? Provider incentives, capacity constraints and patient outcomes - Ingrid Huitfeldt (Statistics Norway, Research Department, 2018)
Healthcare providers' response to payment incentives may have consequences for both fiscal spending and patient health. This paper studies the effects of a change in the payment scheme for hospitals in Norway. In 2010, payments for patients discharged on the day of admission were substantially decreased, while payments for stays lasting longer than one day were increased. This gave hospitals incentives to shift patients from one-day stays to two-day stays, or to decrease the admission of one-day stays. I study hospital responses by exploiting the variable size of price changes across diagnoses in a difference-in-differences framework. I find no evidence that hospitals respond to price changes, and capacity constraints do not appear to explain this finding. Results imply that the current payment policy yields little scope for policymakers to affect the healthcare spending and treatment choices.
Keywords: H51; H75; I11; I18; 330; Provider incentives; hospital reimbursement; price response; capacity constraints